The Effect of Weight Training on The Push Index and Achievement of the 400m Freestyle Over 20 Years - Abbas, Moayad Jasem; Hussein, Ehab Dakhel (Journal of Physical Education, 2026)
The study aimed to prepare exercises for men's 400-meter freestyle runners and to identify the mechanical variables of the thrust index, and the achievement of the research sample, and to identify the effect of weightlifting exercises on the thrust index and the achievement of the men's (400m) freestyle runner between the test (pre-post-test) of the research sample. The researcher hypothesized that statistically significant differences would exist between the pre- and post-tests in favor of the post-test for both the kinematic variable (propulsive index) and performance achievement in the research group. The research population consisted of track and field athletes specializing in the 400-meter event in Maysan Governorate during the 2023 sports season, totaling five (5) runners who competed in championships organized by the Iraqi Athletics Federation. The researcher recommended the use of weighted training exercises due to their effective role in developing muscular strength and subsequently improving athletic performance. The study also recommended utilizing the findings and generalizing them to speed runners, particularly those specializing in the 200-meter event, across all age categories. The researcher concluded that the designed training program using weighted exercises had a significant positive effect on both the propulsive index and performance achievement.